Development of mobile based technology transfer application system to empower the small ruminant farmers - SENTHILKUMAR, S; MANIVANNAN, C; SURESHKANNAN, S (The Indian Journal of Animal Sciences, 2021)
Mobile app is one of the means to strengthen the bridge between research system and farming system. Hence, the present study has focused to identify and prioritize the information needs of small ruminant farmers to develop mobile based application software. Data were collected from 40 researchers of Tamil Nadu Veterinary and Animal Sciences University, 60 extension personnel of the State Animal Husbandry Department and 100 small ruminant farmers of Tirunelveli district by questionnaire method. The responses for each item were measured on a five point continuum, i.e. most needed, more needed, needed, less needed and least needed. The mean was calculated and the item above the mean, i.e 24 items were considered as the identified needs that include topics on breed and breeding (three), feeding (five), management (five), disease control (six) and marketing (five). Based on the identified and prioritized needs, the contents were framed in Tamil and English languages which includes, video clipping and photos collection. Accordingly, a mobile based application software was developed in android platform in order to impart the scientific knowledge of small ruminant farming system in local language to the end users. Perception on the usefulness of developed android based mobile app was captured among 60 randomly selected small ruminant farmers and 60 extension personnel who had android mobile phone that constituted a sample size of 120. The overall perception of the extension personnel (4.1) and farmers (4.0) on the mobile app ranged from most satisfactory to satisfactory.